2019
DOI: 10.1108/arch-11-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Active learning for the promotion of students’ creativity and critical thinking

Abstract: Purpose The purpose of this paper is two-fold: first, it highlights the importance of the presence of active teaching experiences in architecture courses. Such experiences can lead to an improvement in the teaching of technical disciplines, such as structural engineering. Second, it purports to demonstrate the relation and interaction between the active teaching strategy here presented and the learning outcomes required by the study programme. Design/methodology/approach The paper reports an active didactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Prince (2004) has defined active learning as any instructional method, the core elements in which are student activity and engagement in the learning process. Sgambi et al (2019) showed that active learning pedagogy can promote students' creativity and critical thinking when applied to college courses (in their case a structural design course) that are conducted in a passive way.…”
Section: Privacy Needs In a Classroom Settingmentioning
confidence: 99%
“…Prince (2004) has defined active learning as any instructional method, the core elements in which are student activity and engagement in the learning process. Sgambi et al (2019) showed that active learning pedagogy can promote students' creativity and critical thinking when applied to college courses (in their case a structural design course) that are conducted in a passive way.…”
Section: Privacy Needs In a Classroom Settingmentioning
confidence: 99%
“…Most of the educators agree that learning is a cognitive process of acquiring knowledge and information through experiences (Sgambi et al, 2019). Our students have changed radically.…”
Section: Active Learning: the Most Appropriate Learning Methodsmentioning
confidence: 99%
“…Addressing active learning strategies (Sgambi et al, 2019), highlight the importance of active experiences which can lead to improving the teaching of technical subjects, such as structural engineering within the architectural curriculum. Their work demonstrates the relationship between active learning and the educational outcomes mandated by the overall provision.…”
Section: Knowledge Spaces In Architecture and Urbanismmentioning
confidence: 99%